The modern view on the surgical treatment of nephrolithiasis - R. V. Royuk; S. K. Yarovoy; G. A. Aksenov (Вестник урологии, 2023)
The choice of surgical treatment for nephrolithiasis remains a matter of debate. The article is a literature review dedicated to a comparative analysis of the efficacy and safety of extracorporeal shock-wave lithotripsy (ESWL) and endoscopic methods for the treatment of nephrolithiasis. The literature review was based on the analysis of articles published in the PubMed / MEDLINE, and eLibrary databases. Sixty publications on the topic of the review were analysed. As a result of data analysis, endoscopic therapies have a significant advantage over ESWL with comparable safety. The development and dissemination of less invasive techniques such as mini-percutaneous nephrolithotripsy and ultra-mini-percutaneous nephrolithotripsy in the future may change the approach to the surgical treatment of any form of nephrolithiasis.